2020
DOI: 10.1007/s42452-020-03797-6
|View full text |Cite|
|
Sign up to set email alerts
|

Exploring the potential of black gram (Vigna mungo) flour as a fat replacer in biscuits with improved physicochemical, microstructure, phytochemicals, nutritional and sensory attributes

Abstract: High fat intake is associated with various health disorders. Therefore, there have been continued efforts to reduce the fat content in food products and replace it with various fat replacers. In the present study, the effect of black gram (Vigna mungo) flour (BGF) as a fat replacer in biscuits at different concentrations (10, 15, 20, 25, and 50% w/w) was explored. The proximate functional, rheological, microstructural, phytochemical, antioxidant, nutritional, and sensory properties of the flour and biscuits sa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 57 publications
1
5
0
Order By: Relevance
“…Blackgram dal contains more than 20% protein, which is complementary to vegetable protein and also supplements protein in the cereal based low protein diet. Besides, it contains sugars, dietary fibers, starch, minerals, vitamins and essential amino acids (1,2). Interestingly, leguminous pulse crops including blackgram sustain their growth by establishing a symbiotic association with Rhizobium, which fix atmospheric nitrogen in the root nodules (3)(4)(5)(6)(7).…”
Section: Introductionmentioning
confidence: 99%
“…Blackgram dal contains more than 20% protein, which is complementary to vegetable protein and also supplements protein in the cereal based low protein diet. Besides, it contains sugars, dietary fibers, starch, minerals, vitamins and essential amino acids (1,2). Interestingly, leguminous pulse crops including blackgram sustain their growth by establishing a symbiotic association with Rhizobium, which fix atmospheric nitrogen in the root nodules (3)(4)(5)(6)(7).…”
Section: Introductionmentioning
confidence: 99%
“…A similar trend was observed by Szkudlarz et al [38] in cookies enriched with polyphenols from grape pomace. Similarly, Saeed et al [39] observed decreased L* and b* values and increased a* values for biscuits containing black gram (Vigna mungo) flour. Lower values of b* (larger blue content) can be explained by the higher content of total phenolic compounds identified in the samples containing 25%, 50%, 75%, and 100% black rice flour.…”
Section: Color Analysis Of Rice Crackersmentioning
confidence: 82%
“…Table 5 shows the total phenolic compounds (TPC) present in the rice crackers. Because of their anti-inflammatory, anti-radical, and antioxidant properties, these substances contribute to human health protection [39]. Results showed that BRC was linked to higher total polyphenol concentrations by 58.04%, 34.60% free polyphenols, and 73.95% bound polyphenols.…”
Section: Total Phenolic Composition Of Rice Crackersmentioning
confidence: 99%
“…Therefore, the quest for healthy and functional alternatives has been a significant focus in the food industry (Yuksel & Kayacier, 2022). In response to these factors, there is an urgent need to replace hydrogenated fats with ingredients that not only enhance the quality but also the nutritional value of bread (Saeed et al., 2020). Currently, various alternatives have been explored as fat substitutes in the baking industry.…”
Section: Introductionmentioning
confidence: 99%
“…Currently, various alternatives have been explored as fat substitutes in the baking industry. These alternatives include black gram flour (Vigna mungo) (Saeed et al, 2020), wheat bran fibers (Enric et al, 2018), polydextrose and maltodextrin (Sudha et al, 2007), chia seed mucilage (Fernandes & Salas-Mellado, 2017), powdered inulin, inulin gel, and Simplesse (O'brien et al, 2003), yuja fruit peel pectin (Citrus junos) (Lim et al, 2014), among others. However, it is relevant to note that, as mentioned by Boff et al (2022), the benefits provided by these substitutes depend on their characteristics, the type of processing employed, and the degree of substitution, whether total or partial.…”
Section: Introductionmentioning
confidence: 99%